Using Carbohydrate Interaction Assays to Reveal Novel Binding Sites in Carbohydrate Active Enzymes. - Darrell Cockburn; Casper Wilkens; Adiphol Dilokpimol; Hiroyuki Nakai; Anna Lewińska; Maher Abou Hachem; Birte Svensson (PLoS ONE, 2016)
Carbohydrate active enzymes often contain auxiliary binding sites located either on independent domains termed carbohydrate binding modules (CBMs) or as so-called surface binding sites (SBSs) on the catalytic module at a certain distance from the active site. The SBSs are usually critical for the activity of their cognate enzyme, though they are not readily detected in the sequence of a protein, but normally require a crystal structure of a complex for their identification. A variety of methods, including affinity electrophoresis (AE), insoluble polysaccharide pulldown (IPP) and surface plasmon resonance (SPR) have been used to study auxiliary binding sites. These techniques are complementary as AE allows monitoring of binding to soluble polysaccharides, IPP to insoluble polysaccharides and SPR to oligosaccharides. Here we show that these methods are useful not only for analyzing known binding sites, but also for identifying new ones, even without structural data available. We further verify the chosen assays discriminate between known SBS/CBM containing enzymes and negative controls. Altogether 35 enzymes are screened for the presence of SBSs or CBMs and several novel binding sites are identified, including the first SBS ever reported in a cellulase. This work demonstrates that combinations of these methods can be used as a part of routine enzyme characterization to identify new binding sites and advance the study of SBSs and CBMs, allowing them to be detected in the absence of structural data.